DEVELOPMENT MATHEMATICAL CREATIVE THINKING ABILITY PROBLEMS ON THE TOPICS OF FRACTIONS FOR 7 GRADE STUDENTS - Kesumawati, Nila (Jurnal Dosen Universitas PGRI Palembang)
Abstract Â This research aims to generate mathematical creative thinking ability in material fractions for 7th grade students of SMP valid and practical. This research is formative evaluation type of development research. The subjects research is 7th grade students of SMP. The technique of collecting data which is used in this research are walkthrough in order to constructively know the content validity of this questions and the terminology; and document is to ascertain the practicality of this questions. Based on the result of the data analysis, it concluded this research has produced a product mathematical creative thinking ability questions in material fractions for 7th grade students of SMP valid and practical. The validity is reflected from result of validatorâs assessment which stated that the questions have already been good in content (it is based on the curriculum and mathematical creative thinking ability indicators), in construction (develop mathematical creative thinking ability, rich of concepts, based on the level of the 7th grade students), and in language (based on the correct spelling of EYD, no double interpretation of questions, the limitation of questions and clear answers). It is practically shown from the trial test result to one-to-one and small group students where most of students can understand the questions well. Â Keywords: mathematical creative thinking ability, material fractions, the development of questions